Hyperinsulinemia: an early biomarker of metabolic dysfunction - Vaidya, Rama A.; Desai, Sharvari; Moitra, Panchali; Salis, Sheryl; Agashe, Shubhada; Battalwar, Rekha; Mehta, Anushree; Madan, Jagmeet; Kalita, Soumik; Udipi, Shobha A.; Vaidya, Ashok B. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction: Hyperinsulinemia in the absence of impaired glucose tolerance and normal HbA1c is considered indicative of pre-diabetes. Very few Indian studies have focussed on hyperinsulinemia particularly in young adults. The present study examined the fasting and 2-hour stimulated glucose and insulin levels vis-à-vis their HbA1c levels in young adults. Methods: This was a cross–sectional study conducted on adolescents and young adults aged 16-25 years living in Mumbai, India. The participants attended various academic institutions and were those who underwent screening as the first step of a clinical trial for studying the efficacy of almond intake in prediabetes. Results: Among this young population (n=1313), 4.2% (n=55) of the participants were found to be prediabetic (ADA criteria) and 19.7% of them had HbA1c levels between 5.7%-6.4%. However, almost, 30.5% had hyperinsulinemia inspite of normal blood glucose levels and normal HbA1c. Among those with HbA1c<5.7 (n=533), 10.5% (n=56) participants had fasting insulin>15 mIU/L and a higher percentage (39.4%, n=260) had stimulated insulin above 80 mIU/L. These participants had higher mean anthropometric markers than those with normal fasting and/or stimulated insulin. Conclusion: Hyperinsulinaemia in the absence of impaired glucose tolerance and normal HbA1c may provide a much earlier indicator of detection for risk of metabolic disease and progression to metabolic syndrome and diabetes mellitus.